Synthesis Of Palm-Based Trimethylolpropane Esters And Their Potential Use As Lubricant Basestock - Yunus, Robi'ah (2003)
The synthesis of new palm based polyol esters as the biodegradable base stock for lubricant production was conducted via chemical transesterification of palm based methyl esters with trimethylolpropane, 2-ethyl-2-(hydroxymethyl)- 1 ,3-propanediol (TMP). Both palm oil (POME) and palm kernel methyl esters (PKOME) were used as the starting materials and sodium methoxide as the catalyst. The reactions were carried out under different temperatures (80 to 140°C) and vacuum pressures (0.1 to 500 mbar). Palm based TMP esters containing 98% w/w triesters was successfully synthesized in 45 minutes under 10 mbar vacuum, T=1 20°C, and 3 .9: 1 molar ratio of POME to TMP. While the effect of methyl esters to TMP ratio was minimal, the optimum molar ratio was found at 3.5 :1 and 3.8 :1 in palm kernel and palm oil TMP ester synthesis respectively. The amount of catalyst required was less than 1.0% w/w of the total mass of reactants. The optimal reaction conditions were: temperature, BO°C for POME and 1 20°C for PKOME; vacuum, 20 mbar; catalyst, sodium methoxide at 0.7% (w/w); POME:TMP, 3.8:1; PKOME:TMP, 3 .5:1; duration,1hour. Analysis o f the reaction products was performed using GC with a high temperature capillary column, SGE HT5 operated at a temperature gradient of 6°C/min starting from 80°C to 340°C. Before injection, the sample was derivatized with N,O-Bis(trimethylsilyl)trifluoroacetamide (BSTFA) in ethyl acetate at 40°C for at least 10 min. This procedure provided a complete separation of the reaction products: TMP, palm based methyl esters, monoesters, diesters and triesters.